Solving discrete time heterogeneous agent models with aggregate risk and many idiosyncratic states by perturbation - Christian Bayer; Ralph Luetticke (Quantitative Economics, 2020)
This paper describes a method for solving heterogeneous agent models with aggregate risk and many idiosyncratic states formulated in discrete time. It extends the method proposed by Reiter (2009) and complements recent work by Ahn, Kaplan, Moll, Winberry, and Wolf (2017) on how to solve such models in continuous time. We suggest first solving for the stationary equilibrium of the model without aggregate risk. We then write the functionals that describe the dynamic equilibrium as sparse expansions around their stationary equilibrium counterparts. Finally, we use the perturbation method of Schmitt-Grohé and Uribe (2004) to approximate the aggregate dynamics of the model.
Keywords: C63; E32; 330; Numerical methods; heterogeneous agent models; linearization; in-complete markets